Технології протидії малорозмірним безпілотним літальним апаратам - Гура, А. С. (ХНУРЕ, 2025)
The development of counter-UAV technologies focuses on detecting, classifying, and neutralizing small unmanned aerial vehicles (UAVs) to mitigate security threats. Modern systems utilize radar, acoustic sensors, and AI-powered optical recognition for accurate identification. Neutralization techniques include electronic jamming, interception drones, and directed energy weapons. Automated control systems enhance real-time response, integrating data from multiple sensors. The combination of satellite-based tracking and networked defense systems further improves detection and interception capabilities. This study examines advanced UAV defense strategies, highlighting the role of AI, sensor fusion, and adaptive technologies in enhancing security and operational efficiency.
Keywords: малорозмірний БЛА; протидія малорозмірним БЛА